Tratamento de efluente contendo metomil e imidacloprido em reator hermético fotolítico solar - Balsan, Lucas (2019)
In line with the mandatory possession of the decontamination yard for individuals and legal entities that practice aerial spraying of pesticides, provided for in Normative Instruction N° 02 established in Brazil by the Ministry of Agriculture, Livestock and Supply (MAPA) in 2008, this study developed and evaluated an improved hypothetical model of the yard installation required, called the retention reservoir, solarization and evaporation of wash water from agricultural aircraft spray tanks. The system which was characterized by a hermetically sealed photolytic system to ensure occupational safety, with the use of solar radiation as a renewable energy source, which aims to mitigate contamination risks and energy costs in the treatment of effluents with pesticides. Sunlight and heat can activate and accelerate the degradation of metomil and imidacloprid pesticides in mixed solution. The experiment compared the reference samples in the dark at 24±1 °C (R) with treatments carried out in three reactors, which consisted of a hermetic dark reactor (EH), with matt black dyed aluminum cap to enhance radiation absorption. and heat generation, an airtight light reactor (CH), open for light transmittance through a clear borosilicate glass cover, to promote the greenhouse effect and a light open reactor (CA), exposed to the atmosphere and radiation to mimic the constructive aspect required by the MAPA Normative Instruction, which submits the effluents to evaporation. The contribution of radiation on the thermodynamic variation of the reactors was evaluated according to the inherent peculiarities of their constructive aspects, using thermocouple sensors for the effluent thermometry in static regime. The environmental variables of temperature and relative humidity, and dewpoint temperature were measured by means of a datalogger sensor, and the illuminance was read through a lux meter for later conversion of lux to radiation in the power unit. in W.m-2 , for comparison with data obtained from a weather station near the experiment. High performance diode array liquid chromatography was used to determine the residual concentrations of pesticides obtained by averaging triplicate samples of each pesticide in the mixed solution for 13 days of effluent solarization. The tests showed that the EH reactor does not degrade the studied pesticides and the AC reactor concentrates them as the effluent evaporates, forming a more toxic effluent than the original, which generates occupational health risks and biotic environment. The CH reactor was the only one effective in reducing concentrations, with low first and second order kinetic constants and satisfactory determination coefficients, with half-life estimates of 68 and 17 days for metomil and imidacloprid, respectively. The results demonstrate that direct photolysis is not efficient in reducing the concentrations of the studied pesticides and suggest that methods based on photothermocatalytic oxidation processes, using visible light sensitive photocatalysts and with positive effect on thermal increment efficiency, be included in the process required by the decontamination yard.